Alkaline ceramidase 1 is essential for mammalian skin homeostasis and regulating whole‐body energy expenditure. Issue 3 (30th May 2016) - Liakath‐Ali, Kifayathullah; Vancollie, Valerie E; Lelliott, Christopher J; Speak, Anneliese O; Lafont, David; Protheroe, Hayley J; Ingvorsen, Camilla; Galli, Antonella; Green, Angela; Gleeson, Diane; Ryder, Ed; Glover, Leanne; et al.
Abstract: The epidermis is the outermost layer of skin that acts as a barrier to protect the body from the external environment and to control water and heat loss. This barrier function is established through the multistage differentiation of keratinocytes and the presence of bioactive sphingolipids such as ceramides, the levels of which are tightly regulated by a balance of ceramide synthase and ceramidase activities. Here we reveal the essential role of alkaline ceramidase 1 ( Acer1 ) in the skin. Acer1 ‐deficient ( Acer1 −/− ) mice showed elevated levels of ceramide in the skin, aberrant hair shaft cuticle formation and cyclic alopecia. We demonstrate that Acer1 is specifically expressed in differentiated interfollicular epidermis, infundibulum and sebaceous glands and consequently Acer1 −/− mice have significant alterations in infundibulum and sebaceous gland architecture. Acer1 −/− skin also shows perturbed hair follicle stem cell compartments. These alterations result in Acer1 −/− mice showing increased transepidermal water loss and a hypermetabolism phenotype with associated reduction of fat content with age. We conclude that Acer1 is indispensable for mammalian skin homeostasis and whole‐body energy homeostasis. © 2016 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.